Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques